ANALISIS KESULITAN PEMAHAMAN KONSEP ALAT OPTIK PADA SISWA KELAS VIII SEMESTER GENAP SMP NEGERI 3 METRO TAHUN PELAJARAN 2012/2013 - Fitriani .; HRA Mulyani (Jurnal Pendidikan Fisika, 2014)
The purpose of this research to know form of difficulties were experienced by students looked form cognitive domain and questionsettlement stage. The subject of this research was student of grade VIIIc of junior high school 3 Metro academic year 2012/2013 the total of 33 students. Data capture technique used essay test. Data analysis was done by qualitative by identification, tabulation, describtion, and interpretationsteep. Base on analysis can be knowed that the most dominant difficulties were looked from question settlement stage that was operated stage the rules or the laws as much as 73%. Students difficulties were looked from coqtinive domain in ability stage such as knowledge, comprehension, application, and analysis. Difficulties in cognitive domain the most dominant wasexperienced by students are in analysis ability stage as much as 91%. To overcome the difficulties, the teacher is adviced in order that learning the most important to physic concept are felt difficult, that are aplication stage and analysis.